Understanding Different Approaches to ECE Pedagogy through Tensions - Kangas Jonna; Ukkonen-Mikkola Tuulikki; Harju-Luukkainen Heidi; Ranta Samuli; Chydenius Heidi; Lahdenperä Jaana; Neitola Marita; Kinos Jarmo; Sajaniemi Nina; Ruokonen Inkeri (MDPI, 2022)
The concept of pedagogy is the key to understanding pedagogy in early childhood education (ECE) in the Nordic countries, which are known for their high quality of life and education. However, in ECE, there are several different approaches toward pedagogy and it can be said that pedagogy is a multidimensional and dynamic concept. In this paper, the different approaches to pedagogy are defined and reconceptualized through an integrative literature analysis focusing on scientific papers and research reports of the concept. Five approaches to pedagogy were constructed: pedagogy through interaction, pedagogy through scaffolding, pedagogy through didactics, pedagogy through expertise, and pedagogy through future orientation. The identified tensions and elements within the five approaches are presented. Finally, the shared elements among these pedagogical approaches are presented in a dynamic model.